1994
DOI: 10.22358/jafs/69829/1994
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bacterial amino acid contribution to ileal digesta from pigs using <sup>35</sup>S and DAPA marker techniques

Abstract: A study was conducted using two duodenal and ileal cannulated, 45 kg gilts, to determine the bacterial amino acid contribution to amino acids in ileal digesta by using 35 S and diaminopimelic acid (DAPA) as bacterial protein markers. Both the 35 S and DAPA marker techniques are based on the assumption that a representative purified bacterial pellet is collected from ileal digesta samples. The 35 S technique was modified from previous methods by isolating a specific methionine sulphone marker fraction. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The percentages of IP6 to total P in vegetable feedstuffs used in our study were well within the range of 50-85%, as reported by LANTZSCH (1990), EECKHOUT and DE PAEPE (1994) and POINTILLART (1994). This means that the relative contribution of Po to the issue of P digestibility of vegetable feedstuffs, can be quite considerable.…”
Section: Partition Of P In Diets Ileal Digesta and Faeces And Breakdsupporting
confidence: 89%
See 2 more Smart Citations
“…The percentages of IP6 to total P in vegetable feedstuffs used in our study were well within the range of 50-85%, as reported by LANTZSCH (1990), EECKHOUT and DE PAEPE (1994) and POINTILLART (1994). This means that the relative contribution of Po to the issue of P digestibility of vegetable feedstuffs, can be quite considerable.…”
Section: Partition Of P In Diets Ileal Digesta and Faeces And Breakdsupporting
confidence: 89%
“…Partition of N in the ileal digesta of pigs in UD-N, WS-N and BED-N, similar to the present results, has been reported by other researchers: 10-16%, 62-67% and 17-27%, respectively (DIERICK et al 1983) and 17-23%, 43-62% and 22-40%, respectively (DIERICK et al 1990). Also studies of POPPE et al (1983), DROCHNER (1984), DUGAN et al (1994), BARTELT et al (1997) andCAINE et al (1997) show that 20 to 30% of N in ileal digesta originates from bacterial N. Therefore, bacterial fermentation processes in the terminal ileum should not be underestimated. Dense populations of culturable anaerobic bacteria (8.3×10 9 to 8.8×10 9 per g of digesta) were found by JENSEN and JÖ RGENSEN (1994) in the last third of the small intestine, indicating that substantial microbial activity takes place in that portion of the gut in pigs.…”
Section: Partition Of N In the Ileal Digestamentioning
confidence: 97%
See 1 more Smart Citation
“…However, the apparent ileal CP digestibilities of the diets fed in the study by Schulze et al (1994) ranged from 84.0 to 88.9%, which are higher than values reported in the studies by Huang et al (1999). The bacterial nitrogen content in ileal digesta of pigs was also determined by Wuensche et al (1991), Dugan et al (1994), and Caine et al (1999). In some of the studies, quantitative contributions (g/d) were not reported.…”
Section: Resultsmentioning
confidence: 57%
“…Bacteria were isolated from the pooled digesta and fecal samples as described by Dugan et al (1994). Bacterial nitrogen was quantified using diaminopimelic acid (DAPA) as an indicator and calculated on the basis of 26.4 mg DAPA/g bacterial nitrogen according to Wuensche et al (1991).…”
Section: Chemical and Statistical Analysismentioning
confidence: 99%